Moving up North - Olivette Otele (Conserveries Mémorielles)
The article examines the experiences of a few people of African descent in Britain, from economic migrants to refugees and asylum seekers in the last part of the 20th century and early 21st century. Analysing how notions such as the Mediterranean with its historical colonial legacies have been re-appropriated and given way to the term the Black Mediterranean, allows us to understand the way the history of migration from Europe to Africa was linked to the idea of conquest and progress, while 20th and 21st century stories of migration from Africa to Europe are associated with invasion and disorder. The stories of newcomers to Europe, allow us to look at the way several narratives compete. The article is aimed at demonstrating that 20th and 21st century histories of resilience and recovery from trauma, challenge the overrepresentation of stories of deceptions or victimhood. Using archival material from the Refugee Council in London, the article analyses how bureaucracy, policies and politics, amplified by public opinion and media interventions, have in fact derailed the stated aim of integration of these populations. Yet, A few stories of the experiences of Africans who settled in Wales, one of Britain’s regions, paint a different picture that departs from negative ‘loud voices’.